Relações (des)educativas entre o sindicalismo propositivo e o Estado no Brasil (1990-2000): contradições de uma experiência - Affonso, Claudia Regina Amaral (2007)
This research endeavours to investigate the contradictions commonly found in CUT trade unionists participation in State forums, panels and commissions throughout the 1990 s and 2000 s motivated by CUT s concepts of citizenship and pro-positivism. The corpus of this investigation was, therefore, obtained from experiences these commissions had throughout Brazil. The paramount hypothesis lies upon the contradictions derived from the process of disunionization provoked by the change of the recent productive model. Furthermore, this may be associated not only with CUT s adherence to the classical formulations of Social Democracy, but also with entrepreneurial Neo-liberalism. Consequently, this entire situation resulted in a shift of discourse, as well as practice, of a New Unionization in Brazil.